A DESCRIPTIVE STUDY OF THE WRITTEN RECOUNT TEXT PRODUCTION BY SECOND GRADE STUDENTS OF SMP N 5 JEPARA IN 2010/2011 ACADEMIC YEAR - SARI, INDAH PUSPITA (2011)
This research paper aims at describing the elements used in writing recount text produced by the second year students of SMP N 5 Jepara and the problems faced by the students in writing recount text. In this research, the writer uses descriptive research. The object of the study is recount text produced by the second year students of SMP N 5 Jepara. The data of the research are field note, script interview, and document. The data sources are taken from events, informant, and document. In collecting data, the writer uses observation, document, and interview. The techniques for analyzing data are (1) reduction of the data, (2) display of the data, (3) verifying the data. The result of the analysis shows that there are three elements used in recount text, namely (a) social function of recount text, (b) generic structure of recount text, and (c) lexicogrammatical feature of recount text. There are twenty two variations in writing recount text produced by the students. Two variations in the social function of recount text. Seven variations in the generic structure of recount text. Thirteen variations in lexicogrammatical features of recount text. Besides, the students are lack of vocabulary, so the students use dictionary in writing recount text. Problems faced by the students are (a) incapability of the students, (b) student's difficulties in mastering the component of descriptive text, (c) student's difficulties in looking for their ideas in writing, and (d) limitation of vocabulary.